Pengaruh Harga, Kualitas Produk, Dan Lokasi Terhadap Keputusan Pembelian Rumah subsidi Pada Perumahan BTN The Green Lando 2. - Kurnia, Lela; Bahri Dg. Parani , Syamsul; Syarifuddin, Umar; Wanti, Sri (JURNAL MANAJEMEN MOTIVASI, 2026)
This study examines the effects of price, product quality, and location on subsidized housing purchase decisions at BTN The Green Lando 2 Housing Estate. Using a quantitative survey approach, data were collected from 297 consumers selected through random sampling and analyzed using multiple linear regression. The results show that price, product quality, and location have positive and significant effects on purchase decisions, both individually and simultaneously, with an R² value of 0.701. These findings imply that developers should maintain affordable pricing, improve housing quality, and ensure strategic locations to enhance consumer purchasing decisions and competitiveness in the subsidized housing market.